Illuminating a Tragic Miasma in Shepard’s A Particle of Dread - Thomas, Benjamin (Université d'Ottawa / University of Ottawa, 2021)
Sam Shepard was a playwright who used a variety of stories and styles to explore and understand the country he called home, The United States of America. This thesis launches the process of understanding how Greek tragedy had influenced the work of Shepard in his explorations by looking at Shepard’s final play before his passing, A Particle of Dread (Oedipus Variations). Using the concept of miasma that has been established as important to Greek tragedy to analyze A Particle of Dread and its primary source work, Oedipus Rex, this thesis reveals the extent of the ancient tragic form’s presence in Shepard’s last play. To do so, I approach the work in a combination of theory and practice. I first use dramaturgical analysis of Oedipus Rex, to explain what tragic role miasma has in Sophocles’ play. This is followed by a mirrored dramaturgical analysis of A Particle of Dread to uncover and compare what place miasma (and therefore tragedy) has in Shepard’s play. Following this is the review and analysis of five performance workshops exploring scenes of Shepard’s play which used a combination of performance and lighting to physicalize that dramaturgical work so as to further it and hopefully reveal new aspects through their embodiment. This dramaturgical and practical work results in the discovery of how and to what end Shepard has chosen to use the Grecian content style to analyze and commentate on Western society. The work also offers the chance to compare how the engagement with pollution has changed from the characters of 5th Century BCE Greece to 2014 America, and what that might mean for 2020 onwards.
Keywords: Sam Shepard; A Particle of Dread; Miasma; Oedipus Rex; Pharmakos; Lighting Design; Semiotics; Dramaturgy; Stage lighting; Greek tragedy; Contamination; Performance studies; Theatre Workshops; Plague; Adaptation; Sophocles; American Theatre; Oedipus; University of Ottawa theses -- 2021; Thesis